Measuring Disinflation Credibility in Emerging Markets : A Bayesian Approach with An Application to Turkey - Rebucci, Alessandro; Rossi, Marco (Washington, D.C. : International Monetary Fund, 2004)
This paper presents an empirical measure of disinflation credibility and discusses its evolution in Turkey since the 2001 crisis. The results indicate that credibility has improved markedly over this period, boding well for the future of disinflation in Turkey.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet